Characteristic of Eco-Biologycal and Economic Value of Wedgefish (Rhynchobatus Australiae) in Tanjung Luar, East Lombok - Ayesha Hafizh; Mohammad Mukhlis Kamal; Luky Adrianto; Hollie Booth (PT. Publikasiku Academic Solution, 2023)
White Spotted Wedgefish (Rhynchobatus australiae) is one of the member Elasmobranch family which is categorized as an endangered species. The R. australiae is the main target by fishers in Tanjung Luar and Maringkik Island. This study was aimed to analyze ecobiological aspect and to estimate economical incentive value of R. australiae fisheries in Tanjung Luar. The Total of 616 samples were collected from Tanjung Luar Fishing Port from 2017-2021, consisting of 64 males and 552 females. Total 150 fisher respondents from Tanjung Luar and Maringkik Island were interviewed. R-Studio software was used to estimate the ecobiological aspects based on life history parameters. Contingent Valuation Method (CVM) and Discrete Choice Experiment (DCE) were used to estimate economical incentive. The result show that the average length of R. australiae was 213,12 ± 2,63 (cmTL) which is accordance with the regulation. However, the sample of R. australiae was dominated by immature size fish. The growth rate of female R. australiae was lower and have a longer lifespan than male. The condition of R. australiae in Tanjung Luar waters was categorized as biological overfishing. The value of Total Willingness to Pay (WTP) for R. australie conservation was Rp11.226.000/month, whereby the value for individual was Rp.62.340/person. Education and income are the most significant variables affecting WTP.